The Lost Gambit: The Third War between Israel and Egypt, its Causes and Lessons - Alek D. Epstein (Vestnik MGIMO-Universiteta)
Yevgeny Maximovich Primakov knew the Middle East so well as, perhaps, nobody else in Russia did: he worked in Cairo from 1965 till 1969 and visited the city regularly after that period of time. He was personally acquainted with all of the highest representatives of Egyptian political and military elite. He had visited Israel multiple times since August, 1971. Five PrimeMinisters of the Jewish state (Golda Meir, Yitzhak Rabin, Menachem Begin, Shimon Peres, Benjamin Netanyahu) were his interlocutors in different years. Whatever views and powers he had in different years of his extremely intensive and multifaceted activity, the Middle East lacks very much statesmen of such magnitude and with such depth of understanding of geopolitical and regional processes which distinguished Yevgeny Maximovich, to the memory of whom the current essay is devoted. The June War of 1967 year, which is called in Western and Israeli historiography the Six-Day War, has radically changed the Middle East. Dozens of books and hundreds of scientific articles on this war have been published. The current research demonstrates the central role of Egyptian leaders in the onset of the war which nobody sought for. These lead-ers were driven by considerations and interests of pan-Arab solidarity which significantly contradicted in this case the interests of Egypt itself. By analyzing the causes of the war of June 1967 between Egypt and Israel it is proved that they laid to a certain significant extent beyond the context of bilateral relations of these countries.The tragic experience of June 1967 is important nowadays when it is taken for granted that a new war between Israel and Egypt could not erupt because these countries have nothing to divide after the return of the Sinai Peninsula. Once upon a time, in March 1957, Israel has already withdrawn its forces from the Sinai. The same situation of lack of territorial claims did not prevent abrupt escalation of conflict in May 1967 and the following outbreak of hos-tilities. Another important lesson is that security of any country, including Israel, cannot be guaranteed neither by deployment of the “blue helmets” nor by receiving American guaran-tees. As events of the second half of May 1967 demonstrated, both UN forces and American authorities were ready to shirk when the task of war prevention was most acute.